2012
DOI: 10.5505/tjb.2012.49469
|View full text |Cite
|
Sign up to set email alerts
|

The effect of zinc on ethanol-induced oxidative stress in rat liver

Abstract: Aim Zinc is known as an essential trace element and has antioxidant functions. This study was planned to investigate the effects of zinc on oxidative stress induced by ethanol in the rat liver tissue. Methods: Thirty-nine male rats were divided into four groups as control, ethanol (EtOH), zinc (Zn), ethanol plus zinc (EtOH+Zn). The control group (n=10) were injected intraperitoneally (i.p.) with 0.9% saline, EtOH group (n=10) with 2g kg/day ethanol, Zn group (n=10) received orally, ZnSO 4 .7H 2 O at a dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Histological changes on kidney which were different from those effects on liver, however Zn reduced histological changes either in (H.D) or (L.D). These results were in conformity with those reported by Duran et al [17] who reported that Zn supplementation might have a protective effect from cigarette smoke-induced nephrotoxicity in rats and Mansour and Mossa [37] who observed that Zn had resulted in pronounced ameliorating effect against chlorpyrifos-induced kidneys damage in male and female rats. Also effects of S.honey with Zn in (H.D) or (L.D) together reduced IM effect that induced histological changes on kidney.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Histological changes on kidney which were different from those effects on liver, however Zn reduced histological changes either in (H.D) or (L.D). These results were in conformity with those reported by Duran et al [17] who reported that Zn supplementation might have a protective effect from cigarette smoke-induced nephrotoxicity in rats and Mansour and Mossa [37] who observed that Zn had resulted in pronounced ameliorating effect against chlorpyrifos-induced kidneys damage in male and female rats. Also effects of S.honey with Zn in (H.D) or (L.D) together reduced IM effect that induced histological changes on kidney.…”
Section: Discussionsupporting
confidence: 93%
“…It exerts its antioxidant effects indirectly by maintaining membrane structures, involving in the structure of SOD increasing the metallothionein concentrations and competing with redox reactive metals, iron and cuprous for critical binding sites [54]. It founds studies of indicate to role of Zn as antioxidant activity against toxicity that induced hepatorenal and hematological toxicity by Al-Sabaawy [6], Ambali et al [7], Duran et al [17], El-Ashmony [19], Kilic et al [32], Mansour and Mossa [37] and Samir et al [45].…”
Section: Introductionmentioning
confidence: 99%